1999
DOI: 10.1007/s001340051016
|View full text |Cite
|
Sign up to set email alerts
|

Volume-dependent compliance in ARDS: proposal of a new diagnostic concept

Abstract: C(SLICE) was not constant in patients with ARDS/ALI whose lungs were ventilated according to consensus conference recommendations. The proposed diagnostic concept may serve as a new tool to obtain a standardized estimation of respiratory system compliance within V(T) non-invasively without interfering with ongoing mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 41 publications
3
63
0
2
Order By: Relevance
“…The nonlinear behavior of the P/V relationship over a commonly used VT has been described for inflation compliance in surfacant-depleted animals [25]. Furthermore, in patients with acute lung injury [26] and in surfactantdepleted isolated rabbit lungs [27] respiratory system compliance, calculated during uninterrupted ventilation using multilinear regression analysis, has also been shown to be V dependent. To the best of the authors9 knowledge, this study is the first showing that in ARDS patients ventilated with commonly used VT, nonlinear P/V is also present during deflation.…”
Section: Discussionmentioning
confidence: 99%
“…The nonlinear behavior of the P/V relationship over a commonly used VT has been described for inflation compliance in surfacant-depleted animals [25]. Furthermore, in patients with acute lung injury [26] and in surfactantdepleted isolated rabbit lungs [27] respiratory system compliance, calculated during uninterrupted ventilation using multilinear regression analysis, has also been shown to be V dependent. To the best of the authors9 knowledge, this study is the first showing that in ARDS patients ventilated with commonly used VT, nonlinear P/V is also present during deflation.…”
Section: Discussionmentioning
confidence: 99%
“…Mols et al suggested that the intra-tidal compliance-volume curve, calculated by the SLICE method (Guttmann et al, 1994), was able to indicate the ongoing recruitment and overdistension of alveoli in the lung (Mols et al, 1999). The shapes of the Fig.…”
Section: Optimizing Peep With Lung Mechanicsmentioning
confidence: 99%
“…compliance-volume curves are classified into three categories: 1) a decrease in slope indicates overdistension; 2) an increase in slope indicates recruitment; 3) a quasi-horizontal compliance-volume curve indicates a suitable PEEP setting (Mols et al, 1999). However, the method has not yet been evaluated for clinical relevance.…”
Section: Optimizing Peep With Lung Mechanicsmentioning
confidence: 99%
“…Mols et al [2] propose a concept for ventilator setting concerning the intratidal compliance-volume curve determined on the basis of the SLICE method: First, they translate the "S-shape" pressure-volume curve into its first derivation, the trapeziform compliance-volume curve. After that, they define six different shape categories ( Fig.…”
Section: Introductionmentioning
confidence: 99%